THE EFFECTIVENESS OF QUILLBOT APPLICATION ON STUDENTS’ GRAMMAR MASTERY - Hasibuan, Annisa Zahra (JURNAL ILMU PENDIDIKAN, 2024)
A lot of students had problem to arrange English sentence into grammar espesially in Simple Present Tense and Simple Past Tense, so they lost their consentrate in learninng English because there are forms that occur when composing sentences in tenses or other rules, including the form of time rules and the verbs used. This research aims to convey students' achievement to take advantages of QuillBot application, especially on grammar mastery and with the existance of QuillBot application students could manage the time to translate and fix their lack on grammar. The researcher had taken two clases randomly class XI MPLB 1 and XI MPLB 3 which consists of 40 students each class. The researcher uses a test as an instrument. The test instrument included a pre-test and a post-test. The design of this research was quantitative research with experimental research methods. Result of sample could be calculated as like t0 was 6,24 and the degree of freedom was 78. In addition, the value of Ttable in significance level was 1,699. Researcher concluded that T-test was bigger than T-table (6,24>1,699) and Ha was accepted and H0 was rejected because in this progressed one of classes was given the treatment to observe what a significantly affects of QuillBot application for that class.